Serum zinc levels and efficacy of zinc treatment in acne vulgaris: A systematic review and meta‐analysis. Issue 6 (15th September 2020) - Yee, Brittany E.; Richards, Phillip; Sui, Jennifer Y.; Marsch, Amanda Fleming
Abstract: Oral and topical zinc have been used for the treatment of acne, but there is a lack of definitive evidence for their efficacy. (a) To determine if mean serum zinc levels differ between acne patients and controls and (b) to determine the efficacy of zinc preparations in the treatment of acne. A systematic review and meta‐analysis was performed according to recommended PRISMA [Preferred Reporting Items for Systematic Reviews and Meta‐Analyses] guidelines. Subjects with acne had significantly lower serum zinc levels compared to controls. Patients who were treated with zinc had a significant improvement in mean inflammatory papule count compared to those who were not treated with zinc. There was no significant difference in the incidence of side effects in zinc supplementation vs comparators. Acne patients have decreased serum zinc levels. Zinc is effective for the treatment of acne, particularly at decreasing the number of inflammatory papules, when used as monotherapy or as an adjunctive treatment.